Server-based positioning system using Bluetooth low energy technology for tracking assets in hospitals - Brito, Diogo; Leiva-Marcon, Lionel; Paiva, Sara (International Journal of Engineering and Technology, 2018)
In this paper we present a server-based positioning system to track assets in a hospital environment, using Bluetooth low energy technology. The need to easily and quickly find equipment is undeniable and can sometimes be a life or death situation. We present the system architecture and the components we rely on to calculate distance and equipment coordinates. The main purpose of this solution is to allow medical personnel to find an equipment through a desktop computer in the hospital floor. We also present tests made with several materials that are present in a hospital environment and that can influence the signal. Â Â Â